IoT-Based Automatic Transfer Switch System Design on Solar Home System - Sutopo, Angela Michelle; Prastomo, Niki; Bayuntara, Putu Gandhi Aditya (International Journal of Integrated Engineering, 2024)
The challenge hybrid system power sources face is switching from one source to another. This transfer is required to anticipate the depletion of energy sources in the battery owing to unfavorable weather, such that the solar panels do not receive sufficient sunlight. An automatic switching process with minimal time lag is required to maintain the continuity of the electrical energy flow. In addition, there is a growing need to analyze the energy consumption in certain areas and periods. This project designed and built an Internet of Things (IoT) based Automatic Transfer Switch (ATS) system. The ATS prototype uses the Arduino MEGA 2560 microcontroller to switch the power source and the ESP32 DevKit V1 microcontroller to send the data logger to the IoThingsHub cloud platform for monitoring systems that are useful for sustainable ecosystems. The sensor exhibited accuracies of 99.8% for voltage and 96.5% for current readings. The ATS prototype could switch between power sources with an average time lag of 47 ms. The results of the field trials show that the ATS prototype design utilized solar photovoltaic for approximately 26% of the usage, with a 100 Ah 12V battery system and three 100 Wp solar panels in sunny/partly cloudy conditions for 50 W lamp loads.